The mucosal adhesion receptor alpha4beta7 integrin is selectively increased in lymphocytes stimulated with beta-lactoglobulin in children allergic to cow's milk - Eigenmann, P A; Tropia, L; Hauser, C (Journal of allergy and clinical immunology, 1999)
It has been shown in mice that the integrin alpha4beta7 directs the migration of memory T cells into the gut-associated lymphoid tissue. However, little is known about T-cell homing mechanisms in children with food allergies. We investigated the expression of this and other integrins in children with different manifestations of cow's milk allergy (urticaria, atopic dermatitis, and wheezing). PBMCs were stimulated with beta-lactoglobulin, 1 of the major allergenic proteins in cow's milk, and tetanus toxoid. Integrin expression was studied by flow cytometric analysis after 1 week of culture. We found significantly higher expression of the alpha4beta7 integrin in cells from patients compared with control subjects with no allergies (P =. 005) when beta-lactoglobulin was used to stimulate the cells. alpha4beta7 integrin was also expressed at significantly higher levels in beta-lactoglobulin-stimulated cells than in tetanus toxoid-stimulated cells (P =.005). The alphaEbeta7 and the alpha4beta1 integrins were not upregulated by allergen stimulation. Most alpha4beta7 integrin-expressing cells were identified as CD4(+) T cells. These results show that alpha4beta7 integrin expression after stimulation with beta-lactoglobulin correlates with the presumptive site of cow's milk sensitization (ie, the gut-associated lymphoid tissue but not with the site of symptoms of cow's milk allergy).